Big Data and Security c - Tian, Yuan.; Ma, Tinghuai; Khan, Muhammad Khurram; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book constitutes the refereed proceedings of the First International Conference on Big Data and Security, ICBDS 2019, held in Nanjing, China, in December 2019. The 37 revised full papers and 12 short papers were carefully reviewed and selected out of 251 submissions. The papers included in this book cover topics in cybersecurity & privacy, big data, blockchain & internet of things, security in cloud and fog computing, and artificial intelligence/ machine learning security.
Cybersecurity & Privacy -- Big Data -- Blockchain & Internet of Things -- Security in Cloud and Fog Computing -- Artificial Intelligence/ Machine Learning Security.
Keywords: Computers; Computer communication systems; Architecture, Computer; Data encryption (Computer science).; Computer security; Artificial intelligence; Information Systems and Communication Service; Computer Communication Networks; Computer System Implementation; Cryptology; Systems and Data Security; Artificial Intelligence